2015
DOI: 10.1002/hed.23875
|View full text |Cite
|
Sign up to set email alerts
|

Dental implants in irradiated versus nonirradiated patients: A meta‐analysis

Abstract: The purpose of the present meta-analysis was to test the null hypothesis of no difference in dental implant failure rates, postoperative infection, and marginal bone loss for patients being rehabilitated by dental implants and being previously irradiated in the head and neck region versus nonirradiated patients against the alternative hypothesis of a difference. The study suggests that irradiation negatively affects the survival of implants, as well as the difference in implant location (maxilla vs mandible), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
71
0
19

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(93 citation statements)
references
References 78 publications
(297 reference statements)
3
71
0
19
Order By: Relevance
“…Literature shows that implant failure is low and equal for during‐ablative‐surgery and postponed‐placement protocols (3% to 10%) . Some authors speculate that in the during‐ablative‐surgery‐protocol, backscattering might increase the risk of implant failure or osteoradionecrosis because of higher irradiation doses in the bone adjacent the implants, although no in vivo studies so far have demonstrated such negative effects.…”
Section: Discussionmentioning
confidence: 99%
“…Literature shows that implant failure is low and equal for during‐ablative‐surgery and postponed‐placement protocols (3% to 10%) . Some authors speculate that in the during‐ablative‐surgery‐protocol, backscattering might increase the risk of implant failure or osteoradionecrosis because of higher irradiation doses in the bone adjacent the implants, although no in vivo studies so far have demonstrated such negative effects.…”
Section: Discussionmentioning
confidence: 99%
“…Reports and reviews on failed implants or insufficient osseointegration after/during radiotherapy for both hip joints and dental implants indicate risks of implant failure or loss of the implant upon irradiation, most probably due to tissue damage. These risks increase with increasing irradiation dose . This has been questioned in some recent reviews and studies, and patients that undergo radiotherapy have been recommended dental implant therapy if following some guidelines (e.g., strict monitoring) .…”
Section: Introductionmentioning
confidence: 99%
“…Reduced tissue healing capacity leads to osteoradionecrosis, necrotic bone exposure, and pathological fracture in response to tissue trauma; thus, with reduced healing ability and osteoradionecrosis in response to injury, the implant survival rate may be reduced for the maxillofacial oral cancer patients who have undergone radiotherapy treatment. [123456]…”
Section: Introductionmentioning
confidence: 99%